PSYCHOSOCIAL IMPACT OF POLYCYSTIC OVARY SYNDROME ON WOMEN’S QUALITY OF LIFE: BODY IMAGE, MENTAL HEALTH, AND FERTILITY-RELATED DISTRESS - Anastazja Orłowa; Kamil Turlej; Aleksandra Oparcik; Laura Kurczoba; Anna Baranowska; Anita Pakuła; Marta Cieślak; Klaudia Martyna Patrzykąt; Kinga Szyszka; Julia Pawłowska (International Journal of Innovative Technologies in Social Science, 2025)
Background: Polycystic ovary syndrome affects 8-13% of women of reproductive age and is one of the most common endocrine disorders. Although PCOS has traditionally been viewed as a reproductive and metabolic pathology, accumulated evidence demonstrates significant psychological and social consequences affecting women’s quality of life. Aim: This literature review systematizes current scientific evidence on the psychological and social impact of PCOS on women’s quality of life, with emphasis on body image concerns, mental health comorbidities, and fertility-related distress. Methods: We searched PubMed/MEDLINE, Embase, Web of Science, PsycINFO, and Cochrane Library databases for relevant literature. The review included systematic reviews, meta-analyses, cohort studies, and qualitative studies. No time restrictions were applied; we included both recent research and foundational publications from earlier years. Results: Women with PCOS show much higher body dissatisfaction than healthy women. Visible symptoms like excess hair growth and acne, combined with weight control problems, clash with cultural ideals of femininity and cause ongoing emotional distress. The prevalence of depressive and anxiety symptoms is elevated, with this association being multifactorial and involving both biological mechanisms (insulin resistance) and psychosocial factors. Eating disorders represent a particular area of vulnerability, with concerns about weight and body shape occupying a central role. Reproductive difficulties create a severe emotional burden, exacerbated by sociocultural contexts where motherhood is considered an essential part of female identity. Conclusion: PCOS has significant psychosocial consequences requiring a comprehensive approach to patient management. A medical model focused exclusively on physical symptoms is insufficient. Integration of mental health screening and a multidisciplinary approach are necessary for providing quality care to women with PCOS.